Formação de professores de espanhol: algumas reflexões - Carvalho, Kelly Cristiane Henschel Pobbe de [UNESP] (My University, 2011)
The article is concerned with the professional development of teachers of Spanish as a foreign language (SFL). The study aimes at: (a) articulating a context for discussion on issues related to teaching SFL, and (b) identifying the main difficulties related to linguistic content and methodological aspects that students who are teachers have in regard to their professional development as SFL teachers. Participants were undergraduate student-teachers of Modern Languages who participate in the project Centro de Línguas e Desenvolvimento de Professores (CLDP). Data analysis was conducted according to the Qualitative-Interpretive Paradigm and Action Research. The results show that participation in the CLDP Project creates an academic context that facilitates the professional development of SFL teacher as the activities complement the quality of their academic education.

Este artigo traz reflexões acerca do processo de desenvolvimento profissional de professores de espanhol/LE. O estudo objetivou (a) articular um espaço de reflexão acerca de questões referentes ao processo de ensino-aprendizagem de E/LE, e (b) identificar as principais dificuldades relacionadas a conteúdos linguísticos e aspectos metodológicos que alunos-professores apresentam no processo de desenvolvimento profissional como professores de E/LE. Os participantes foram alunos-professores, graduandos-estagiários em Letras, que participam do projeto do Centro de Línguas e Desenvolvimento de Professores (CLDP). A metodologia adotada foi a Pesquisa-Ação. Os dados analisados revelam que a participação no projeto proposto pelo CLDP tem cumprido o papel de formar um amplo espaço acadêmico de desenvolvimento profissional do professor de espanhol/LE.
The formation of Spanish teachers: some reflections
Keywords: Spanish teaching; Teachers’ formation; Methodological and linguistic difficulties; Formação de professores; Ensino-aprendizagem do espanhol